The Social Policy of Combating Domestic Violence in Georgia and Lithuania - Šumskaitė, Lina; Namicheishvili, Salome (Socialinė teorija, empirija, politika ir praktika, 2017)
Domestic violence is perceived as one of the most severe violations of human rights and gender inequality. It has negative psychological, social and economic impact on the victim. In seeking to combat violence of an intimate partner, laws against domestic violence were implemented in many European countries. Two countries, Lithuania and Georgia, are compared in the article. Even if they have different locations and patriarchal traditions, the common past of belonging to Soviet Union unites them.The article compares the political measures and their impact on the solution of the domestic violence problem. Even the laws criminalizing domestic violence were implemented in 2006 in Georgia and in 2011 in Lithuania. The problem of domestic violence remains a top issue in both countries. The amount of reported domestic violence events maintains a high level; however, the investigated cases level remains low. Still, a high level of unreported domestic violence cases remain in both countries. Insufficient shelters for women victims of violence remain a problem in both countries.